Evaluation of urban afforestation of Manaus City by her residents - Lins Neto, Nelson Felipe de Albuquerque; Souza, Paulo Roberto Pires de; Viana, Álefe Lopes; Mari, Maikel Lamego Guimarães; Medeiros, Suzana Helen da Silva (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
The aim of this study was to quantify the perception of afforestation in the city of Manaus by their residents and it relates to investments made by the municipal government. Data were obtained from 647 online electronic questionnaires distributed among users of social networks on the internet and smartphones. The results indicated that only 3% of participants considered very good afforestation in Manaus and 42% very poor, and the north and east areas with 48% to 61% the worst of the city. As for the benefits of afforestation, 72% indicated thermal comfort as the most important. The biggest concern was the risk of tipping, followed by interference power grid, with 25 and 24%, respectively. The most remembered species were pau pretinho, ipê and fruit trees. Of the respondents, only 65% would be willing to contribute whit some value for afforestation, even with 71% of those considering the insufficient public investments for expansion and maintenance of green spaces. When compared to cities like São Paulo and Campo Grande items as a percentage of GDP invested in municipal afforestation , R/km2 and R/capita , were always lower.